First total synthesis of (+)-Neplanocin B - Comin, M.J. (2005)
(+)-Neplanocin B ((+)-5), the unnatural isomer of a minor component of the neplanocin family of antibiotics was enantioselectively synthesized starting from D-ribono-1,4-lactone. This synthetic strategy employed (+)-9-[(1R, 2R, 5S)-5-Benzyloxy-3-(benzyloxy)methyl-2-hydroxycyclopent-3-en-1-yl] -6-chloropurine (compound 7) as an advanced synthetic intermediate. ©ARKAT.